ANALISIS KOREKSI FISKAL ATAS LAPORAN KEUANGAN PADA PT. PROTEKSINDO UTAMA MULIA - Ernawati Ernawati; Syahyuni Syahyuni (Universitas Tridinanti, 2022)
This study aims for valid and reliable knowledge about the extent to which PT. Proteksindo Utama Mulia Group in complying with the applicable laws and regulations with fiscal improvements to the 2019 financial statements and describing matters related to improvements. The result of data analysis for this research case is PT. Proteksindo Utama Mulia Group has not prepared its fiscal financial statements in accordance with the applicable tax regulations. This can be seen from the positive correction of Rp.657,987,726,- and the negative correction of Rp.1,831,720,- As a result of the positive and negative corrections, there was an increase in the amount of commercial profit from Rp.1,205,390,009,- to Rp. .1.861.546.015, - which means that there is an increase in profit of 54.4% which is recognized by the fiscal.Keywords: Fiscal correction; financial statements